Pengembangan Aplikasi Open Trip Berbasis Web Studi Kasus Perusahaan Uneetha Tour and Travel - Dhony Octaviano; Yulia Ery Kurniawati (UNIVERSITAS KALBIS, 2022)
This study aims to develop a web-based open trip application for Uneetha Tour and Travel. In this application, customer service can enter data, change data and also delete open trip event data. For customers, you can register by filling out the form contained in the application and uploading photos as proof of payment. This application development uses the rational unified process method where the developer performs system modeling (inception), system design (elaboration), system implementation (construction) and system delivery (transition). This application development uses PHP programming language with Codeigniter framework and MySQL database. The result is a web-based open trip application that can minimize errors and can see the remaining quota